Epithelioid haemangiosarcoma of the thyroid gland. Report of six cases from a non-Alpine region - Ryska, A; Ludvíková, M; Szépe, P; Böör, A (Histopathology, 2004)
AIM: To report a series of six cases of thyroid haemangiosarcoma (HAS) from a non-Alpine region. METHODS AND RESULTS: The patients were four females and two males, aged 54-81 years (average 68 years). The tumours presented as large haemorrhagic masses (diameter 40-70 mm, average 56 mm) with extensive necrosis. Histologically, they were composed of polymorphous epithelioid cells with vesicular nuclei and abundant eosinophilic cytoplasm with occasional intracytoplasmic lumina. Mitotic activity was high. Tumor cells expressed vimentin (6/6), CD31 (6/6), FVIII (5/6), CD34 (2/6), and cytokeratins (5/6). One tumour (1/6) over-expressed p53 protein in more than 20% of cells. Ultrastructurally, Weibel-Palade bodies were present (4/6). Clinical follow-up of four patients (range 3-24 months, median 9 months) showed that two of them have died of the disease 0.5 and 3 months after diagnosis, one died of unrelated causes (with 24 months' uneventful follow-up) and one is alive 21 months after operation with no evidence of disease. CONCLUSIONS: Although thyroid HAS is usually regarded as an extremely aggressive neoplasm with a dismal prognosis similar to anaplastic carcinoma, one of our cases suggests that HAS can behave in a less aggressive way. The morphological, immunohistochemical and ultrastructural findings support the hypothesis that thyroid HAS is a distinct entity, unrelated to other thyroid malignancies.
Keywords: Female; lidé středního věku; Reagent Kits, Diagnostic; Mitosis; Weibel-Paladeho granula; Epithelioid Cells; Fatal Outcome; mužské pohlaví; Biomarkers, Tumor; senioři nad 80 let; Humans; Immunoenzyme Techniques; hemangiosarkom; nádorové biomarkery; nádory štítné žlázy; Thyroid Neoplasms; lidé; Hemangiosarcoma; Middle Aged; Weibel-Palade Bodies; imunoenzymatické techniky; Aged, 80 and over; senioři; reagenční diagnostické soupravy; ženské pohlaví; fatální výsledek; mitóza; Aged; epiteloidní buňky; Male